Psychology in Selecting the Characteristics Product Storytelling Influencing the Thai Population - Pinjisuwan, Jeerapat; Tevichapong, Thanita; Wongwien, Nutmanee; Lasamor, Areeya; Aukkarakitpreecha, Kittidech; Thongteerapab, Aonjaree; Thaisom, Rungtip (Journal of Industrial Business Administration, 2020)
The purposes of the study are 1) to study demography on the selection of product storytelling influences on the Thai population 2) to study the behavior of product style storytelling influences on the Thai population and 3) to study psychology in selecting the characteristics of product storytelling influencing the Thai population This research is a descriptive research. The samples are 400 Thai people in Bangkok. The cluster random sampling method is used. The research instrument is a questionnaire. Statistics are used to analyze data are percentage, frequency, mean, standard deviation the inferential statistics used to test hypotheses are including Chi- square and One- way ANOVA. The findings reveal that behavioral dimension, most consumers perceive product storytelling through seeing. The consumers see the story of the product through the social media channels of the store. Psychological dimension, most of consumers have psychological factors that affect the story telling to the product. The overall of perception, attitude and motivation through storytelling are at a high level. Learning aspects that affect the purchase of products through storytelling is at the highest level. The hypotheses testing has found that demographic factors on the selection of product storytelling influences on the Thai population do not correlate with behavioral factors on the selection of product storytelling influences on the Thai population. Moreover, the demographic factors on the selection of product storytelling influences on the Thai population is different from psychological factors in selecting the characteristics of product storytelling influencing the Thai population.